Effectiveness of folk games’ application in formation of pedagogic specialties girl students’ value orientations on physical culture - M.I. Mayevsky (Physical Education of Students, 2015)
Purpose: to determine effectiveness of structurally meaningful model of formation of girl students’ value orientations on physical culture. Material: in the research control group (28 girl students) and experimental group (30 girl students) participated. We used sociological questioning, testing of physical and theoretical fitness. Results: It was found that combination of four blocks (theoretical, methodic, practical and managerial) is optimal for technology of model realization. It ensures impact on physical and spiritual-intellectual sides of girl students. Conclusions: it is recommended to practice active immersion in folk traditions and customs of Ukraine with girl students. It permits to form girls’ psychological and social readiness for conducting of cultural measures. Motor activity in personal and future professional functioning makes elements of such measures.